Practice education placements for undergraduate social work students in the corporate sector of the Western Cape metropole : an exploratory investigation - Brown, Iris Cathrine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSocialWork)--Stellenbosch University, 2002.